Emergence of New Creatures: A Consequence of Breeding and Reproduction. (The Past and Future Human Creatures) (International Journal of Scientific Research and Management (IJSRM), 2017)
To think of the first creature is to think of the first reaction, this is so because everything is a product of some thing; except in the case where nothing became something; but nothing is something, so they are one thing. This scientific literature dares to prove that everything an individual creature becomes, is the result of the creation processes that occurred during the various stages of reproduction reactions from the cell to the organism level; this is the visible gradual unit of evolution which permits distant resemblance between ancestors of thousand years offspring.